Anxiety and Defense Mechanism Portrayed by the Main Character in Puss in Boots: The Last Wish Novel (2022) - Kharisma, Angel; Valiantien, Nita Maya (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2025)
The aim of this study is to explore the anxiety and defense mechanism depicted in Puss as the main character from the novel Puss in Boots: the last Wish using theory of anxiety and defense mechanism from Sigmund Freud. The researcher employed descriptive qualitative method within psychoanalysis approach. The research data are words, phrases, and sentences referring to the Puss’s experinces of anxiety and defense mechanism that collected through reading, highlighting and note-taking. The results of this study show that Puss experiences anxiety namely: realistic anxiety from his environment and the Big Bad Wolf; neurotic anxiety from the thought of Big Bad Wolf would punishing him; and moral anxiety from violating moral codes. Then, Puss defense mechanisms to cope with his anxiety were: repression through running away and gaining comfort from Dog; denial to reject bitter reality; sublimation by change his hesitation into positive mindset; rationalization by justifying his action; and compensation to surpass his weakness in other area. Therefore, these mechanisms are able to help Puss getting out of his fearful state and eventually step forward to live his final life bravely.